Analisis Penerapan Jaminan pada Pembiayaan Mudharabah dan Musyarakah di Perbankan Syariah - Astriah; Muhammad Kamal Zubair (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2021)
Sharia Banking is a financial institution that has sharia principles and applies Islamic law in making decisions. In the form of disbursement of funds that can be accessed by using mudharabah and musyarakah financing, the concept of mudharabah and musyarakah has the principle of trust (trust) but in practice Islamic banks apply guarantees in their financing, this is not in accordance with the initial principle of mudharabah and musyarakah, namely the trust system. The purpose of this study is to determine the difference between mudaraba and musyarakah in Islamic banking and to determine the application of existing guarantees in Islamic banking. This type of research uses a library research approach. The primary data source is the book "Sharia Guarantee Law and Its Implementation in Islamic Banking in Indonesia and the book Reconstruction of Collateral Law in Mudharabah Contracts" as well as other books related to secondary data sources from books, reports, journals, theses, dissertations, and others related . The data collection technique starts from reading references, then classifying them so that they get conclusions from the questions obtained so that they can answer the problem formulation. The data analysis technique used is the comparative method. The results of this study indicate that: (1) the difference between mudharabah and musyarakah lies in terms of understanding, legal basis, implementation in Islamic banking, capital, business management, ratio, business risk, guarantee and dispute resolution. (2) The principles of mudharabah and musharaka are the principles of trust, but in practice Islamic banks do apply guarantees as a condition in the event of default in the future, the guarantee can replace the losses of Islamic banks through auction. Keywords: mudharabah, musyarakah, guarantee, sharia banking